Reflection On Service-Learning Among Universiti Teknologi Malaysia Students - Zainudin Hassan; Jayanthi Marrimuthu; Tan Meng Lee Vincent; Latha Haridass; Wan Asri Wan Mat (International Journal of Educational Management and Innovation, 2023)
The purpose of service learning is to connect theory and practice in a way that gives students a prospect to both take part in a service activity that meets community needs, as well as reflect on the experience in class to enhance their civic engagement and deepen their understanding of course content. A successful service-learning program requires reflective practice. The School of Education at Universiti Teknologi Malaysia (UTM), Malaysia has been conducting service-learning for many years. Although there is no proper guideline for the students to reflect on their service-learning experiences, students are still expected to do so. The objective in this study are describing service-learning experience. This research study applies case study research method among students’ reflective experiences in service-learning at School of Education in UTM. Data collection was done using qualitative research methodology involving semi structured interviews with UTM postgraduates. Triangulation method used to validate the data and continued with thematic analysis to identify the themes. The findings for every research question have been plotted in diagram. Based on the themes from the findings, a template was proposed for improving service-learning reflection for the students from UTM.